1992
DOI: 10.1246/cl.1992.759
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Electrochemical Properties of the Green Ytterbium(III) and Lutetium(III) Sandwich Complexes of Octabutoxy-Substituted Phthalocyanine

Abstract: The Yb(III) and Lu(III) sandwich complexes of 2,3,9,10,16,17,23,24-octabutoxyphthalocyanine (H2obPc) were prepared and characterized. Those electrochemical properties in CH2Cl2 were studied by means of cyclic voltammetry and absorption spectra in 320–1600 nm region monitored during controlled-potential electrolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 9 publications
2
20
0
Order By: Relevance
“…To further analyze the electrochemical data, potential differences (ΔE° 1/2 ) between the first oxidation and the first reduction processes were determined and found to be 0.36 and 0.55 V vs Ag|AgCl, respectively for 2 a (n DCM) and 2 b (in DMF) (Table ). These ΔE° 1/2 values are comparable to those of LuPc 2 complexes found in literature (Table ) but smaller than the experimentally determined ΔE° 1/2 values for monophthalocyanes containing transition metals which range between 0.78 and 1.71 V vs SCE. A value of ΔE° 1/2 that approaches that of the average value for monomeric phthalocyanines (∼ 1.5 V) is known to reflect weak interactions between the phthalocyanine rings in neutral LnPc 2 complexes .…”
Section: Resultsmentioning
confidence: 94%
“…To further analyze the electrochemical data, potential differences (ΔE° 1/2 ) between the first oxidation and the first reduction processes were determined and found to be 0.36 and 0.55 V vs Ag|AgCl, respectively for 2 a (n DCM) and 2 b (in DMF) (Table ). These ΔE° 1/2 values are comparable to those of LuPc 2 complexes found in literature (Table ) but smaller than the experimentally determined ΔE° 1/2 values for monophthalocyanes containing transition metals which range between 0.78 and 1.71 V vs SCE. A value of ΔE° 1/2 that approaches that of the average value for monomeric phthalocyanines (∼ 1.5 V) is known to reflect weak interactions between the phthalocyanine rings in neutral LnPc 2 complexes .…”
Section: Resultsmentioning
confidence: 94%
“…Therefore, direct metalation of presynthesized low-symmetry Pcs with lanthanide salts is the only rational approach to sandwich complexesw ith the required arrangementoffunctional groups. [40][41][42][43][44][45][46] Therefore, we tentatively explained this specific reactivity of ligand 1 by the presence of two DEG fragments terminated with OH groups. [38,39] Typically,t hese are reactions between H 2 Pcs with corresponding acetates (OAc)ora cetylacetonates (acac) in high-boilingc hlorinated aromatic solvents or alcohols, either in the presence or in the absence of ab ase (DBU or MeOLi).H owever,n either prolonged refluxing of 1 with [Eu(OAc) 3 ]o r[ Eu(acac) 3 ]i nv arious solvents nort he addition of DBU led to the formationo ft he complexes (Scheme 1), andt he UV/Vis spectra of the reaction mixture showedo nly two characteristic Q-bands of the intact ligand 1.…”
Section: Synthesis and Characterization Of Sandwich Metallophthalocyamentioning
confidence: 97%
“…To synthesize THP-protected DD complex 2a,w em etalated 1a with 1.5 equivalents of [Eu(OAc) 3 ]i nr efluxing octanol under the previously reported conditions [44] targeted to form bisphthalocyaninates.H owever,t he reactionw as not selective, and am ixture of DD 2a and TD 3a complexes was formed. Increasingt he ratio of [Eu(OAc) 3 ]/1a to 2.5 [45,46] resulted in the formation of triple-decker 3a as the sole sandwich product.…”
Section: Synthesis and Characterization Of Sandwich Metallophthalocyamentioning
confidence: 99%
“…Another remark refers to the value of the Q band splitting, which is reported to decrease as the interplanar distance increases. [20,28] For (Pc)Lu(CRPc)Lu(Pc) this splitting value is 83 nm with a interplanar distance fixed at 2.9 Å . As our interplanar distance is measured by the crystallographic study (3.17 Å ), we expected a splitting value significantly smaller than 83 nm.…”
Section: Uv/visible Spectroscopymentioning
confidence: 99%
“…lanthanide molecules. [22Ϫ25] Some homoleptic triple-decker sandwich molecules built with three phthalocyanine macrocycles have been reported: (Pc)M(Pc)M(Pc) synthetized by K. Kasuga et al [26] with M ϭ Y, Nd, Gd, Er, and Lu; (Pc)Lu(CRPc)Lu(Pc) with CRPc ϭ crown-ether-substituted phthalocyanine, [27] synthesized by N. Ishikawa and Y. Kaizu who introduced the crown-ether at the periphery of the macrocycle to give these compounds greater solubility, and the M 2 (obPc) 3 (obPc ϭ 2,3,9,10,16,17,23,24-octabutoxyphthalocyanine, M ϭ ytterbium, dysprosium, [28] lanthanum and lutetium [29] ) synthesized by K. Takahashi et al The only reported triple-decker phthalocyanine complexes built around a metal without any f orbitals are the indium complex [30] and, very recently, a red-violet phase of bismuth triple-decker phthalocyanine, [31] both obtained by J. Janczak et al In this report, we present the preparation of a black phase of the same molecule Bi 2 (Pc) 3 , and discuss its crystal and molecular structures, as well as its characterization by FT-IR and UV/Visible spectroscopies.…”
Section: Introductionmentioning
confidence: 99%